Induction of IL-22-Producing CD4+ T Cells by Segmented Filamentous Bacteria Independent of Classical Th17 Cells - Roy, Urmi; de Oliveira, Rômulo S.; Galvez, Eric J. C.; Gronow, Achim; Basic, Marijana; Perez, Laura Garcia; Gagliani, Nicola; Bleich, Andre; Huber, Samuel; Strowig, Till (Frontiers in Immunology, 2021)
The intestinal microbiota modulates IL-22 production in the intestine, including the induction of IL-22-producing CD4+ T helper cells. Which specific bacteria are responsible for the induction of these cells is less well understood. Here, we demonstrate through the use of novel gnotobiotic knock-in reporter mice that segmented filamentous bacteria (SFB), which are known for their ability to induce Th17 cells, also induce distinct IL-17A negative CD4+ T cell populations in the intestine. A subset of these cells instead produces IL-22 upon restimulation ex vivo and also during enteric infections. Furthermore, they produce a distinct set of cytokines compared to Th17 cells including the differential expression of IL-17F and IFN-γ. Importantly, genetic models demonstrate that these cells, presumably Th22 cells, develop independently of intestinal Th17 cells. Together, our data identifies that SFB induces besides Th17 also CD4+ T cell populations, which serve as immediate source of IL-22 during intestinal inflammation.